KONTRIBUSI BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU SDIT ABU BAKAR ASH-SHIDDIQ RAJAPOLAH - Masnil Walidah; Yayan Rudianto; Wahdan Budi Setiawan; Erna Rusmiwati Sukandar; Endang Syarif (Journal of Innovation Research and Knowledge, 2026)
Abstract: The problem in this study relates to the performance of teachers at SDIT Abu Bakar Ash-Shiddiq Rajapolah, which is contributed by organizational culture and work discipline. This study aims to: 1) Identify the organizational culture at SDIT Abu Bakar Ash-Shiddiq Rajapolah, 2) Identify the work discipline at SDIT Abu Bakar Ash-Shiddiq Rajapolah, 3) Determine the teacher performance at SDIT Abu Bakar Ash-Shiddiq Rajapolah, and 4) Analyze the contribution of organizational culture and work discipline to teacher performance at SDIT Abu Bakar Ash-Shiddiq Rajapolah. This research uses a descriptive quantitative method with a preplication approach. The Primary data were collected through the distribution of questionnaires by using a Likert scale to 35 respondents. The analysis tool used, is multiple linear regression analysis. The results show that: 1) The organizational culture at SDIT Abu Bakar Ash-Shiddiq Rajapolah is considered good, 2) The work discipline at SDIT Abu Bakar Ash-Shiddiq Rajapolah is considered good, 3) The teacher performance at SDIT Abu Bakar Ash-Shiddiq Rajapolah is considered good, and 4) Based on multiple linear regression analysis, organizational culture and work discipline, It have a positive and significant contribution to teacher performance